Aluminum / molecular perovskite composite energetic material and preparation method thereof

By using nano-aluminum powder in aluminum/molecular perovskite energy-containing materials, the particle size is controlled at 100±5nm, and combined with the preparation method of perchlorate-based molecular perovskite energy-containing materials, the ignition time of existing materials is solved. The problem of excessive length significantly improves the energy release speed and reliability of the material.

CN119431089APending Publication Date: 2025-02-14CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411583044.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The ignition time of existing aluminum/molecular perovskite energy-containing materials is too long, limiting their application in explosives.

Method used

By replacing metal aluminum powder with nano-aluminum powder, the particle size is controlled at 100±5nm, combined with perchlorate-based molecular perovskite energy-containing materials, aluminum/molecular perovskite composite content is prepared by ultrasonic dispersion and vacuum drying methods by ultrasonic dispersion and vacuum drying. Energy material.

Benefits of technology

It significantly reduces the heat release temperature, accelerates the mass and heat transfer speed of the system, accelerates the energy release speed of energy-containing materials, meets the demand for high heat release capabilities of modern weapons, reduces ignition time, improves reliability and environmental adaptation sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431089A_ABST
    Figure CN119431089A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energetic materials, and discloses an aluminum / molecular perovskite composite energetic material and a preparation method thereof. Wherein the metal aluminum powder is 15-50 parts; 85 to 50 parts of a molecular perovskite energetic material; metal aluminum powder is replaced with nano aluminum powder with the particle size of 100 + / -5nm, so that the ignition time of the energetic material is shortened, meanwhile, the invention discloses a preparation method, a volatile organic solution is used as a dispersing agent, and the molecular perovskite energetic material and the nano aluminum powder are sequentially dispersed into a solvent through ultrasound, so that the energetic material is prepared. And the organic solvent and the mixed composite energetic material are separated in a standing and drying manner, so that the production safety of the energetic material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energetic materials, and in particular to an aluminum / molecular perovskite composite energetic material and a preparation method thereof. Background Art

[0002] Energetic materials are a critical part of military weapons. To fully apply energetic materials to new weapons, the performance of energetic materials must adapt to new changes in all aspects of the military field. It is of great value to develop energetic materials that have good combustion performance, high thermal stability and low production cost. Among them, molecular perovskite energetic materials combine low-cost fuel components and oxidant components through self-assembly strategies to prepare a series of ternary crystals with perovskite structures. They have the advantages of simple preparation process, low raw material cost and less harm to the environment. They are very suitable as a new generation of advanced high-energy materials and are in line with the current development trend of explosives.

[0003] At present, the Chinese patent with application number 202111237795.4 discloses a propellant mixed fuel of molecular perovskite energetic material composite metal aluminum. By mixing the molecular perovskite energetic material with aluminum powder to increase the combustion heat of the energetic material, a fuel calorific value of 8000KJ / Kg to 8500KJ / Kg is obtained. However, when explosives are made from the energetic material, it is found that the general ignition time of the material is between 3-5s, which is not suitable for the production of explosives. For explosives, a long ignition time will bring a series of problems, such as reaction delay, reliability, environmental adaptability and other problems. Therefore, although the existing aluminum / molecular perovskite energetic material has a higher combustion heat, its long ignition time limits its application in explosives. Summary of the invention

[0004] The present invention aims to provide an aluminum / molecular perovskite composite energetic material and a preparation method thereof, so as to reduce the ignition time and improve the application of the aluminum / molecular perovskite energetic material in the field of explosives.

[0005] To achieve the above object, the present invention adopts the following technical solution: an aluminum / molecular perovskite composite energetic material, the raw material components and their mass fractions are as follows:

[0006] Aluminum powder:

[0007] 15-50 servings;

[0008] Molecular Perovskite Energetic Materials:

[0009] 85-50 servings;

[0010] The molecular perovskite energetic material is a perchlorate-based molecular perovskite energetic material, characterized in that the metal aluminum powder is nano aluminum powder, and the particle size of the nano aluminum powder is 100±5 nm.

[0011] Generally speaking, nano aluminum powder is the most common high-energy metal fuel agent in solid fuels. Compared with traditional energetic materials, composite materials based on nano aluminum have the advantages of closer particle contact and can reduce the mass transfer and heat transfer paths in the reaction process. The smaller the particle size of the nano aluminum powder, the closer the contact with the molecular perovskite energetic material, and the higher the efficiency of mass transfer and heat transfer. Therefore, composite nano aluminum powder in molecular perovskite energetic materials is expected to improve the combustion performance and heat release performance of molecular perovskite energetic materials. To reduce the ignition time of aluminum / molecular perovskite composite energetic materials, the main approach is to reduce the particle size of aluminum powder. However, the inventors found in actual work that when the particle size of nano aluminum powder is less than 100nm, the ignition time is shortened as the particle size decreases. When the particle size of nano aluminum powder is less than 100nm, the ignition time of the composite energetic material is prolonged as the particle size decreases. When the particle size of nano aluminum is less than 50nm, the mixed aluminum / molecular perovskite composite energetic material cannot be ignited.

[0012] The beneficial effects of this scheme are: replacing aluminum powder with nano aluminum powder with a particle size of about 100±5nm significantly reduces the exothermic temperature, accelerates the mass transfer and heat transfer rate of the system, and accelerates the energy release rate of the energetic material, meeting the demand for high exothermic capacity in the research and development of modern weapons, reducing ignition time, and reducing reaction delay, thereby improving the reliability and environmental adaptability of aluminum / molecular perovskite composite energetic materials as explosives, and has great application potential.

[0013] Furthermore, the mass ratio of the nano aluminum powder to the molecular perovskite energetic material is 1:4.

[0014] Furthermore, the particle size of the nano aluminum powder is 100 nm. When the particle size is 100 nm, the particle size has the greatest impact on the ignition time, and this size has the most significant impact on its ignition time. This means that at this particle size, the ignition speed or reactivity of the aluminum / molecular perovskite composite energetic material will be particularly affected, and this property is very important for the selection and use of the material in a specific application.

[0015] Furthermore, the types of perchlorate-based molecular perovskite energetic materials are one or more of (H2dabco)[Na(ClO4)3], (H2dabco)[NH4(ClO4)3], (H2dabco)[K(ClO4)3], (H2mpz)[NH4(ClO4)3], (H2pz)[NH4(ClO4)3], (H2hpz)[NH4(ClO4)3], (H2dabco-O)[NH4(ClO4)3], (H2mdabco)[NH4(ClO4)3], (H2dabco)[NH3OH(ClO4)3] and (H2dabco)[NH2NH3(ClO4)3].

[0016] A method for preparing an aluminum / molecular perovskite composite energetic material comprises the following steps: preparing materials, preparing the perchlorate-based molecular perovskite energetic material and nano aluminum powder as described in claim 1, grinding the perchlorate-based molecular perovskite energetic material, and placing it in a volatile organic solvent for ultrasonic dispersion to form a dispersed solution; mixing, adding the nano aluminum powder to the dispersed solution, ultrasonic mixing, and obtaining a mixed solution; standing, allowing the mixed solution to stand, waiting for the nano aluminum powder and the molecular perovskite energetic material to settle to the bottom, pouring out the upper clear liquid, and obtaining a precipitate; drying, evaporating the organic solvent in the precipitate to dryness, and obtaining a target product. The powdered perchlorate-based molecular perovskite energetic material is ground and placed in an organic solvent, and pre-dispersed by ultrasound, so that the perchlorate-based molecular perovskite energetic material is uniformly dispersed in the organic solvent, and then the nano aluminum powder is added, and the mixing is performed by ultrasound, so as to avoid the powdered perchlorate-based molecular perovskite energetic material from agglomerating, affecting the mixing uniformity with the nano aluminum powder, and making the mixing more uniform.

[0017] In addition, compared with the traditional solid-solid mixing method of grinding mixing or equal multiple mixing, this scheme first disperses a large amount of perchlorate-based molecular perovskite energetic material into an organic solvent, and then adds a small amount of nano-aluminum powder into the dispersion system and mixes it by ultrasound, thereby avoiding the aggregation of a small amount of nano-aluminum powder first, resulting in uneven solid-solid mixing. At the same time, the mixing process is safer, laying the foundation for mass production.

[0018] Furthermore, the volatile organic solvent is anhydrous ethanol or ethyl acetate. Taking advantage of the relatively low boiling point of anhydrous ethanol or ethyl acetate, anhydrous ethanol or ethyl acetate is used as a dispersion and mixing medium, thereby facilitating the subsequent evaporation operation.

[0019] Furthermore, the standing time is ≥ 12 hours. By standing for a long time, it is ensured that the aluminum / molecular perovskite composite energetic material can be fully precipitated at the bottom of the container, so that most of the solvent and the aluminum / molecular perovskite composite energetic material are separated in advance, thereby reducing the evaporation time and energy consumption during the subsequent solid-liquid separation.

[0020] Furthermore, the evaporation is vacuum drying. Due to its own nature, energetic materials are flammable and explosive. When facing high temperature or violent collision, there is a certain danger. This solution isolates the composite energetic material from oxygen by vacuum drying, thereby reducing the danger during the operation and laying the foundation for mass production.

[0021] In summary of the above technical features: 1. The present invention provides an aluminum / molecular perovskite composite energetic material and a preparation method thereof. By replacing metal aluminum powder with nano aluminum powder, the ignition time of the aluminum / molecular perovskite composite energetic material is shortened, so that the aluminum / molecular perovskite composite energetic material can be applied to the field of explosives; 2. The present invention overcomes a type of technical prejudice and shortens the ignition time by reducing the particle size of the low-ignition-point component. The smaller the particle size, the shorter the ignition time; 3. The present invention provides a preparation method for energetic materials, which lays a foundation for the mass production of energetic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The SEM image of the aluminum / molecular perovskite composite energetic material prepared in Example 1(a) of the present invention and the SEM image of the molecular perovskite energetic material prepared in Comparative Example 1(b);

[0023] Figure 2 This is an X-ray diffraction pattern of the aluminum / molecular perovskite composite energetic material prepared in Example 1 of the present invention;

[0024] Figure 3 Combustion diagram of the aluminum / molecular perovskite composite energetic material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following is further described in detail through specific implementation methods:

[0026] A method for preparing an aluminum / molecular perovskite composite energetic material comprises the following steps: preparing materials, grinding the molecular perovskite energetic material into powder, placing it in a volatile organic solvent for ultrasonic dispersion, the volatile organic solvent is preferably anhydrous ethanol or ethyl acetate, to form a dispersed solution; mixing, adding nano aluminum powder to the dispersed solution, ultrasonic mixing, and obtaining a mixed solution; standing, the mixed solution is standing for a standing time of greater than or equal to 12 hours, waiting for the nano aluminum powder and the molecular perovskite energetic material to precipitate to the bottom, pouring out the supernatant, and obtaining a precipitate; drying, evaporating the organic solvent in the precipitate to obtain a target product, and the evaporation method is vacuum drying. It should be noted that the material needs to be isolated from the air during the entire preparation process to avoid the material from reacting with the air, introducing additional factors, and affecting the accuracy of the results, that is, the material preparation, mixing, standing, and drying must be isolated from the air throughout the process. In this embodiment, the air isolation method is nitrogen protection, that is, the air is isolated using nitrogen.

[0027] In order to improve the material properties of aluminum / molecular perovskite composite energetic materials, it is necessary to determine the ratio of aluminum powder to molecular perovskite energetic materials through experiments. Using the above preparation method, molecular perovskite energetic materials and ordinary aluminum powder were mixed in ratios of 1:1, 2:1, 3:1, 4:1 and 5:1 to obtain samples 1-5. The exothermic peak temperature, heat release and ignition time were tested to obtain Table 1.

[0028]

[0029] Combining the experimental data of samples 1-5, the exothermic peak temperature and the amount of heat released were analyzed comprehensively. When the mixing ratio of aluminum powder and molecular perovskite energetic material is 1:4, the mixing ratio is better.

[0030] At the same time, in order to shorten the ignition time of energetic materials, the appropriate particle size was determined, and nano-aluminum powders with particle sizes of 200nm, 100nm, 80nm and 50nm were selected and mixed with molecular perovskite energetic materials in a ratio of 1:4 to obtain samples 6-9, and their exothermic peak temperature, heat release and ignition time were tested, and the results are shown in Table 2.

[0031]

[0032]

[0033] From the experimental data in Table 2, it can be seen that when the particle size of aluminum powder decreases from 200nm to 100nm, the ignition time shortens as the particle size decreases. When the particle size is less than 100nm, the ignition time prolongs as the particle size decreases. When the particle size is 50nm, the sample cannot be ignited. Therefore, the ignition time of the aluminum / molecular perovskite composite energetic material can be shortened by reducing the particle size of the aluminum powder. The best particle size of the aluminum powder is 100nm.

[0034] Example 1

[0035] 0.40g molecular perovskite energetic material DAP-1 ((H2dabco)[Na(ClO4)3]) was ground into powder and added into a beaker containing 20ml of anhydrous ethanol, and ultrasonically dispersed for 10min to fully disperse DAP-1 in anhydrous ethanol. Then, a certain mass of 0.1g of 100nm nano-aluminum powder was weighed and added into the solution, and ultrasonically dispersed for 30min, and then placed at room temperature for 12h, and the aluminum / molecular perovskite composite energetic material was obtained after the solvent was evaporated.

[0036] Example 2: The difference between this preparation example and preparation example 1 is that the mass of the molecular perovskite energetic material is 0.30 g (3:1; 75%).

[0037] Example 3: The difference between this preparation example and preparation example 1 is that the mass of the molecular perovskite energetic material is 0.50 g (5:1; 83.3%).

[0038] Comparative Example 1

[0039] The difference between this comparative example and Example 1 is that no nano-aluminum powder mixing preparation is performed, and only the molecular perovskite energetic material DAP-1 is prepared.

[0040] Performance Testing

[0041] The properties of the energetic materials in Examples 1-3 and Comparative Example 1 were tested using the following method.

[0042] Scanning electron microscopy: SEM was used to characterize the morphology of the energetic material samples prepared in Examples 1-3 and Comparative Example 1. The SEM image of the sample in Example 1 is as follows: Figure 1 (a) shows the SEM image of the sample of Comparative Example 1. Figure 1 (b) By comparison, it can be observed that the spherical particles of nano-aluminum adhere to the surface of DAP-1, and the contact between the material particles is closer.

[0043] X-ray diffraction: A powder X-ray diffractometer was used to characterize the phases in Examples 1-3 and Comparative Example 1. The X-ray diffraction pattern of Example 1 is shown in FIG. Figure 2 The aluminum / molecular perovskite composite energetic material prepared in Example 1 shows diffraction peaks of DAP-1 and A1, indicating that the composite energetic material is a physical mixture of nano-aluminum and DAP-1, and the crystal structure of the DAP-1 energetic material is not destroyed.

[0044] Combustion performance: The energetic material is ignited by an ignition device, and the combustion performance of Examples 1-3 and Comparative Example 1 is preliminarily determined by the ignition time of the material and the size of the combustion flame in the ignition experiment.

[0045] Thermal decomposition performance: The thermal decomposition behavior of Examples 1-3 and Comparative Example 1 was studied by TG-DSC method and synchronous thermal analyzer to obtain the thermal decomposition process, exothermic peak temperature and exothermic heat.

[0046]

[0047] It can be seen from the data in Table 3 that the aluminum / molecular perovskite composite energetic material prepared in the present invention has a lower exothermic peak temperature than that before the composite nano-aluminum powder, compared with Comparative Example 1, indicating that the nano-aluminum powder accelerates the heat and mass transfer rate of the system and promotes the thermal decomposition of DAP-1.

[0048] like Figure 3 As shown, the aluminum / molecular perovskite composite energetic material obtained in Example 1 is ignited. After ignition, the burning flame is white, and there are sputtering combustion particles during combustion. The nano aluminum powder increases the intensity of the combustion of the molecular perovskite energetic material.

[0049] The increase in decomposition heat of the aluminum / molecular perovskite composite energetic material compared to before the composite nano-aluminum powder indicates that after the DAP-1 molecular perovskite energetic material is composited with nano-aluminum powder, the contact between the material particles is closer, and the distance of mass and heat transfer between the material particles during the reaction becomes shorter, making the heat release more complete and enhancing the energy release of DAP-1.

[0050] The above is only an embodiment of the present invention, and common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that the technical means for solving the problems in the above-mentioned embodiments of the present invention can be used in combination to solve multiple technical problems at the same time. For those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the scope of protection of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An aluminum / molecular perovskite composite energetic material, characterized in that: The raw material components and their mass fractions are as follows: Aluminum powder: 15-50 servings; Molecular Perovskite Energetic Materials: 85-50 servings; The molecular perovskite energetic material is a perchlorate-based molecular perovskite energetic material, and the metal aluminum powder is nano aluminum powder, and the particle size of the nano aluminum powder is 100±5 nm.

2. The aluminum / molecular perovskite composite energetic material according to claim 1, characterized in that: The optimal ratio of the nano aluminum powder to the molecular perovskite energetic material is 1:

4.

3. The aluminum / molecular perovskite composite energetic material and preparation method thereof according to claim 2, characterized in that: The particle size of the nano aluminum powder is 100 nm.

4. The aluminum / molecular perovskite composite energetic material according to claim 3, characterized in that: The types of perchlorate-based molecular perovskite energetic materials are one or more of (H2dabco)[Na(ClO4)3], (H2dabco)[NH4(ClO4)3], (H2dabco)[K(ClO4)3], (H2mpz)[NH4(ClO4)3], (H2pz)[NH4(ClO4)3], (H2hpz)[NH4(ClO4)3], (H2dabco-O)[NH4(ClO4)3], (H2mdabco)[NH4(ClO4)3], (H2dabco)[NH3OH(ClO4)3] and (H2dabco)[NH2NH3(ClO4)3].

5. A method for preparing an aluminum / molecular perovskite composite energetic material, characterized in that: The method comprises the following steps: preparing materials, preparing the perchlorate-based molecular perovskite energetic material and nano aluminum powder as described in claim 1, grinding the perchlorate-based molecular perovskite energetic material, and placing it in a volatile organic solvent for ultrasonic dispersion to form a dispersed solution; mixing, adding the nano aluminum powder to the dispersed solution, ultrasonically mixing, and obtaining a mixed solution; standing, standing the mixed solution, waiting for the nano aluminum powder and the molecular perovskite energetic material to precipitate to the bottom, pouring out the upper clear liquid, and obtaining a precipitate; and drying, evaporating the organic solvent in the precipitate to dryness, and obtaining a target product.

6. The method for preparing an aluminum / molecular perovskite composite energetic material according to claim 5, characterized in that: The volatile organic solvent is anhydrous ethanol or ethyl acetate.

7. The method for preparing an aluminum / molecular perovskite composite energetic material according to claim 6, characterized in that: The standing time is ≥12 hours.

8. The method for preparing an aluminum / molecular perovskite composite energetic material according to claim 7, characterized in that: The evaporation to dryness is vacuum drying.

Citation Information

Patent Citations

  • Propellant mixed fuel prepared by compounding molecular perovskite energetic material with metal aluminum

    CN113956120A